2019
DOI: 10.1158/0008-5472.can-18-0520
|View full text |Cite
|
Sign up to set email alerts
|

PRL-3 Promotes Ubiquitination and Degradation of AURKA and Colorectal Cancer Progression via Dephosphorylation of FZR1

Abstract: The oncogenic phosphatase PRL-3 is highly expressed in metastatic colorectal cancer but not in nonmetastatic colorectal cancer or noncolorectal cancer metastatic cancers. Although the proinvasive capacity of PRL-3 has been validated in multiple types of cancer, its impact on colorectal cancer progression and the underlying mechanisms remain poorly understood. Here, we report that overexpressed PRL-3 stimulates G 2 -M arrest, chromosomal instability (CIN), self-renewal, and growth of colorectal cancer cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…VHL is an E3 ligase that multimonoubiquitinates AURKA in quiescent cells and targets it for proteasome-mediated degradation under both normoxic and hypoxic conditions [38]. Phosphatase PRL-3 enhances AURKA ubiquitination and degradation in colorectal cancer [34]. Destabilization of AURKA by PRL-3 requires PRL-3-mediated dephosphorylation of FZR1 and assembly of the APC/CFZR1 complex [34].…”
Section: Smad4mentioning
confidence: 99%
See 1 more Smart Citation
“…VHL is an E3 ligase that multimonoubiquitinates AURKA in quiescent cells and targets it for proteasome-mediated degradation under both normoxic and hypoxic conditions [38]. Phosphatase PRL-3 enhances AURKA ubiquitination and degradation in colorectal cancer [34]. Destabilization of AURKA by PRL-3 requires PRL-3-mediated dephosphorylation of FZR1 and assembly of the APC/CFZR1 complex [34].…”
Section: Smad4mentioning
confidence: 99%
“…Phosphatase PRL-3 enhances AURKA ubiquitination and degradation in colorectal cancer [34]. Destabilization of AURKA by PRL-3 requires PRL-3-mediated dephosphorylation of FZR1 and assembly of the APC/CFZR1 complex [34]. PTPRD is a protein tyrosine phosphatase and a tumor suppressor.…”
Section: Smad4mentioning
confidence: 99%
“…AURKA has been defined as a crucial regulator of mitotic chromosome segregation through its catalytic activity [42,43]. The oncogenic phosphatase PRL-3 is upregulated in metastatic colorectal cancer and it interacted with AURKA and FZR1, thus influencing the development of colorectal cancer [44]. It was reported that thiostrepton could reduce FOXM1 target genes expression including AURKA and CCNB1, which contributed to the progression of G2/M cell cycle [45].…”
Section: Discussionmentioning
confidence: 99%
“…FZR1 is considered as a tumor suppressor that are negatively regulated the activation of the MEK/ERK oncogenic signaling cascade 48 . The evidence showed that FZR1 interacted with PRL-3 to regulate the progression of colorectal cancer by controlling the stability of AURKA 49 . These results are consistent with our clinical validation that the expression of FZR1 is correlated with the prognosis and survival of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%